Analysis of time‐dependent dynamics of micropolar fluid subject to Lorentz force, energy flux due to a concentration gradient and viscous dissipation. Issue 6 (11th April 2022) - Das, Nabanita; Ahmed, Nazibuddin; Taid, Bijoy Krishna
Abstract: This study deals with an analysis of the time‐dependent dynamics of micropolar fluid flow subject to Lorentz force, diffusion thermal, and viscous dissipation effect past a uniformly moving semi‐infinite porous plate in the presence of chemical reaction. Expressions of velocity, microrotation, concentration, temperature, skin friction, Sherwood number, and Nusselt number are established and the effect of several parameters on them are represented graphically. Equations governing the flow and heat transfer are solved by adopting the regular perturbation technique. It is noticed that temperature distribution as well as the coefficient of friction is enhanced due to the diffusion thermo effect. It is observed that the microrotation increases with increasing magnetic parameters. Furthermore, the study confirms a drop in fluid concentration under the composition of species.